Preparation and characterisation of metallorganic precursors derived iron oxides on porous silicon layers - Perova, Tatiana (Trans Tech Publications Ltd., Switzerland, 2020)
Porous silicon has generated interest in scientific community after its photoluminescence discovery and thereafter, research was focused on to the chemical functionalization of silicon and subsequent anchoring of nanoparticles onto silicon surface. In the present work, the porous silicon has been effectively modified with magnetic nanoparticles which were prepared through metallorganic approach. The as-fabricated magnetic-porous silicon composites were characterised using FTIR and Raman spectroscopies, Scanning Electron Microscopy (SEM) as well as magnetic measurements.
Materials Science Forum
ICSMEE+ICEESM, Dublin, June 30-July 2 2019
Keywords: Porous silicon; Magnetic nanoparticles; FTIR; Raman spectroscopy; Nanoscience & Materials; Manufacturing Processes (Industrial Engineeri